Maintenance and reliability with focus on aircraft maintenance and spares provisioning - Wikstén, Johan; Johansson, Marcus (2006)
This report is the result of a study performed on maintenance reliability and, its, related issues. Studies of logistic support issues have also been performed to understand its important role in maintenance practice. Due to the extensive topics of maintenance, the focus in this study has been set to the investigation of the possibilities to make use of existing records for improvement in maintenance procedures and in some manner, also spare parts provisioning. The study focuses on the maintenance procedures in the aviation industry and, has been carried out in accordance with aviation regulating authority. The study has been performed at the Division of Operation and Maintenance Engineering at Luleå University of Technology (LTU) during ten weeks in the spring semester of 2006. Sponsor for the study was Luleå FlygTeknik (LFT) which provided material and expertise in aviation maintenance and its procedures. The authors wish to thank every person who has, in one way or another, been contributing or involved in this study. A especially thank you, are directed to the following persons for their participation and for sharing their expertise during the study, they are: Prof. Uday Kumar (examiner LTU), Aditya Parida (supervisor LTU) and Jan Viklund (sponsor and supervisor LFT). Validerat; 20101217 (root)